Klebsiella pneumoniae metabolites enhance Microcystis aeruginosa biomass flocculation. Issue 9 (20th October 2016) - Xu, Liang; Huo, Mingxin; Yang, Wu; Zhou, Dandan; Huo, Hongliang
ABSTRACT: Microcystis aeruginosa is a common aquatic toxin-producing cyanobacterium. This study explores M. aeruginosa biomass recovery using bioflocculation. Bioflocculants produced by Klebsiella pneumoniae significantly enhanced aquatic M. aeruginosa flocculation efficiency. Under neutral and acidic conditions, flocculation efficiency reached 90%, whereas flocculation efficiency was 75% under alkaline conditions. M. aeruginosa flocculation was ion dependent, and Ca 2+ was determined to be the most effective cationic inducer. Negatively charged proteoglycans were identified as the being the functional components in the flocculants. Optimal conditions for M. aeruginosa flocculation were determined using response surface methodology and are as follows: (1) K. pneumoniae bioflocculant dose, 13.3 mg/L; (2) flocculation time, 1.6 hours; and (3) pH = 5 for flocculation of 10 9 cells per litre. Bioflocculation using K. pneumoniae represents a promising method to control development of M. aeruginosa blooms. Further in-field investigations are necessary to fully assess its potential.